Feasibility Evaluation and Optimization of a Smart Manufacturing System Based on 3D Printing: A Review. Issue 4 (26th October 2016) - Chen, Toly; Lin, Yu‐Cheng
Abstract : As a major enabling factor for Industry 4.0, three‐dimensional (3D) printing faces technical and managerial concerns that may hinder its sustainable development. In this study, four technical challenges are reviewed as follows: time‐consuming 3D object design, limited types of usable materials, low precision, and low productivity. Seven managerial concerns are also discussed as follows: 3D object database management, intellectual property rights of 3D printing, business innovation, ubiquitous manufacturing, lean manufacturing, globalization and deglobalization, and feasibility evaluation and optimization. Then, this study asserts that technical challenges should be addressed to ensure the feasibility of a 3D printing application in a manufacturing context, whereas managerial concerns should be addressed to advance and optimize a 3D printing application. Based on the discussion, to maximize profit, a smart manufacturing system based on 3D printing should continually provide 3D objects of interest to customers, or join as many ubiquitous manufacturing networks as possible.